Sistem Informasi E-Borrowing Berbasis Web PT. Telkom Access - MS, OK Mhd Fahri Al-Faruqy; Ramadhani , Fredy Kusuma (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
In the digital age, advancements in information technology play a significant role in optimizing business processes. This study presents the design and implementation of a web-based E-Borrowing Information System tailored for PT Telkom Akses to address inefficiencies in equipment borrowing management. The current manual borrowing process often leads to delays, data inaccuracies, and administrative errors, impacting productivity and transparency. The proposed solution integrates real-time features for booking, managing, and tracking equipment loans. The system employs PHP and MySQL for backend functionality and HTML, CSS, and JavaScript for the user interface, following the waterfall development methodology. To evaluate its effectiveness, the system underwent functionality testing (Black Box Testing) and usability assessments. Results confirm significant improvements in process efficiency, transparency, and administrative accuracy. The system enables users to complete borrowing transactions quickly, with features to monitor equipment status, register personal accounts, and manage data in a structured manner. Additionally, the “Admin Dashboard” enhances overall system supervision through real-time monitoring and efficient management tools. This research highlights the transformative impact of web-based technology on equipment loan management, demonstrating scalability for broader application in similar settings. The study underscores the potential of well-designed information systems to enhance operational efficiency, employee satisfaction, and organizational productivity.